Avaliação do consenso estratégico na área de produção em pequenas empresas - Saes, Elizangela Veloso (2015)
This study evaluates the Strategic Consensus in the production area in small companies in São Carlos through the level of the agreement of managers and operators as for the importance of competitive priorities, structural investments and infrastructure policies, associating this theme research of organizational specificities of those companies that foster the consensus. Therefore, in order to explore these issues, this research examines the theoretical background regarding the Strategic Consensus and the specificities of small firms and presents an exploratory analysis derived from a sample consisting of 58% of the study population, accounting for 38 small businesses analyzed. The observations are based on responses from multiple respondents, which are represented by 55 managers and 117 operators. With the assistance of a statistical software, the analyzes were guided primarily in hypothesis testing by Analysis of Variance, non-parametric tests (Friedman and Adjusted Rank Transform), Correlation Analysis and Clusters Analysis. As main results, it is observed that in general it is possible to understand that there is substantial consensus, highlighting the strategic elements related to quality, flexibility, production and infrastructure polices. In addition, to the sample in question, managers and operators tend to give more importance to the competitive priority quality, to establish as infrastructural police more important delegation of responsibility and the least important to the formation of teams. Nevertheless when explored the organizational characteristics of small business in São Carlos before his behavior with regarding to the profile of the existent consensus, technical knowledge, degree of formalization and number of employees were identified as significant factors for the characterization of these companies. These conclusions enable small companies find out their better strategic positioning in sense of getting a more appropriate pattern in terms of Strategic Consensus, as well as becoming this decision achievable.